Pendampingan Pelatihan Aplikasi Pengolah Kata dan Pengolah Presentasi bagi Siswa SLB Nurul Ikhsan Ngadiluwih - Iqlima Zahari; Natalinda Pamungkas; Gery Gadman Rachmad; Syafira Putri Yuanita; Christiawan Yosua Hertinando; Erba Lutfina; Wildan Mahmud; Erika Devi Udayanti; Ignasius Yoga Puji Hascaryo (Bumi: Jurnal Hasil Kegiatan Sosialisasi Pengabdian kepada Masyarakat, 2024)
Currently, almost everyone must be able to master technology, especially information technology. The progress of information technology is increasingly rapid, nowadays humans are expected to be able to use computers, laptops, gadgets in everyday life. The aim of this activity is to provide assistance and training in word processing applications (Microsoft Word) and presentation processing (Microsoft Power Point) to Nurul Ikhsan SLB children, because their existence in society is often underestimated. The methods used are introduction, implementation and evaluation. The introduction was carried out by conducting observations and interviews to obtain a general overview of Nurul Ikhsan Ngadiluwih SLB with its various activities. Implementation was carried out by providing training and mentoring to SLB students. After this training the students were very enthusiastic and enthusiastic because our presence was able to provide a different color, their computer training activities were only carried out with limited time in the life skills activity agenda, computer life skills were also very limited because their computer staff and infrastructure were also very limited. There were no obstacles experienced during this service, because they were very welcoming of our presence, and hoped that there would be training on other occasions.